CLUSTER MODEL OF FINANCING OF INNOVATIVE DEVELOPMENT OF AGRARIAN SECTOR OF THE CARPATHIAN MACROREGION - Perevozova, I.V.; Sus, T.Yo. (The actual problems of regional economy development, 2018)
The problem of technological re-equipment, scientific and financial support of innovative development remains urgent in the agrarian sector. The advantages of using cluster financing of innovative development of the agrarian sector are substantiated. The agrarian sector is most promising for clustering using a cluster model of financing, because actually every region of the Carpathian macro-region has the unique agricultural potential, which, with its efficient use with the help of a cluster, will provide the development of all its participants, including the financial sector, and will reduce the risks of financing of innovations, and accordingly the credit resources will become more accessible. In modern economic conditions a cluster model of financing is possible on the base of the formation of the banking cluster, which serves as a tool for project financing at the regional level, is noted that. The advantage of the banking cluster that co-operates with an agrarian cluster or agroholding is a mutually beneficial cooperation with regular customers, and also the parties get the stable and reliable partner with significant financial flows. The peculiarities of the forming of financial cluster and a list of possible participants are considered. The list of main tasks concerning the activity of financial clusters in the agrarian sector of the economy is proposed.